Bolivia : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This paper analyzes Bolivia's growth performance with a focus on the regional and sectoral patterns of growth, and examines the sources of growth. It discusses the evolution of the hydrocarbon sector, its importance in the economy, and reforms. It also analyzes the intergovernmental fiscal relations system and changes to the revenue sharing arrangements, and suggests possible areas for reform. It assesses measures of reserve adequacy in Bolivia and also provides a look at the external debt after the applications of the main debt relief plans in the past 10 years.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet